Investigating the influence of varying water regimes on the growth and development and nutritional water productivity of bush tea (Athrixia phylicoides DC.) - Rumani, Muneiwa; Mabhaudhi, Tafadzwanashe; Mandizvo, Takudzwa; Ramabulana, Anza‐Tshilidzi; Madala, Ntakadzeni Edwin; Ramphinwa, Maanea Lonia; Magwaza, Lembe Samukelo; Mudau, Fhatuwani Nixwell (Wiley, 2024)
Bush tea (Athrixia phylicoides DC.) is an indigenous shrub of South Africa known for its medicinal properties. However, due to a lack of comprehensive information to develop suitable irrigation management strategies, the cultivation of bush tea is currently limited to small‐scale operations. Considering this limitation, the current research investigated the effect of water regimes on the growth and development, yield, and nutrient content along with its nutritional water productivity (NWP) under field conditions. The treatment consisted of a crop water requirement (ETa) of 100%, 30%, and the control (stress) in a complete randomized block design (CRBD). Each treatment was replicated three times to ensure robustness and accuracy of the findings. Results demonstrated that the highest gravimetric moisture content readings were found in the control treatment and the lowest in the 100% treatment. Conversely, the 30% ETa treatment significantly (p < 0.05) impacted bush tea's growth, development, productivity, and NWP. However, it was observed that the 100% ETa treatment resulted in a higher biomass yield (259.1 kg/ha) compared to the 30% ETa treatment (171.2 kg/ha) and control (stress) (68.2 kg/ha). The water productivity exhibited notable differences across the varying water regimes. These findings contribute valuable insights for developing appropriate irrigation management strategies to overcome existing limitations in the scale of bush tea production. The research lays the groundwork for future studies and practical applications aimed to foster the sustainable cultivation of bush tea in South Africa.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3004 Crop and Pasture Production; Nutrition; 2 Zero Hunger